Seiberg-Witten Like Monopole Equations on R5 (Journal of Partial Differential Equations, 2011)
We give an analogy of Seiberg-Witten monopole equations on flat Euclidian space R^5. For this we used an irreducible representation of complex Clifford algebra Cl_5. For the curvature equation we use a kind of self-duality notion of a 2-form on R^5 which is given in [1].
Keywords: Seiberg-Witten equations; spinor; Dirac operator